Development of a tiered framework for public health capacity in Canada. (July 2016) - Wallar, L.E.; McEwen, S.A.; Sargeant, J.M.; Mercer, N.J.; Garland, S.E.; Papadopoulos, A.
Highlights: Select SARS reports were qualitatively analyzed for usage of "capacity"/"capacities". Public health capacity can be sub-divided into 17 individual capacity components. These components can be organized into five tiers to build a capacity framework. This framework can be used to guide capacity assessment and building efforts.